Differential Diffusional Properties in Loose and Tight Docking Prior to Membrane Fusion - Witkowska, Agata; Spindler, Susann; Mahmoodabadi, Reza Gholami; Sandoghdar, Vahid; Jahn, Reinhard (Biophysical Journal, 2020)
Fusion of biological membranes, although mediated by divergent proteins, is believed to follow a common pathway. It proceeds through distinct steps, including docking, merger of proximal leaflets (stalk formation), and formation of a fusion pore. However, the structure of these intermediates is difficult to study because of their short lifetime. Previously, we observed a loosely and tightly docked state preceding leaflet merger using arresting point mutations in SNARE proteins, but the nature of these states remained elusive. Here, we used interferometric scattering (iSCAT) microscopy to monitor diffusion of single vesicles across the surface of giant unilamellar vesicles (GUVs). We observed that the diffusion coefficients of arrested vesicles decreased during progression through the intermediate states. Modeling allowed for predicting the number of tethering SNARE complexes upon loose docking and the size of the interacting membrane patches upon tight docking. These results shed new light on the nature of membrane-membrane interactions immediately before fusion.
CRIS-Team Scopus Importer:2020-12-11

Production of isolated giant unilamellar vesicles under high salt concentrations - Stein, Hannah; Spindler, Susann; Bonakdar, Navid; Wang, Chun; Sandoghdar, Vahid (Frontiers in Physiology, 2017)
The cell membrane forms a dynamic and complex barrier between the living cell and its environment. However, its in vivo studies are difficult because it consists of a high variety of lipids and proteins and is continuously reorganized by the cell. Therefore, membrane model systems with precisely controlled composition are used to investigate fundamental interactions of membrane components under well-defined conditions. Giant unilamellar vesicles (GUVs) offer a powerful model system for the cell membrane, but many previous studies have been performed in unphysiologically low ionic strength solutions which might lead to altered membrane properties, protein stability and lipid-protein interaction. In the present work, we give an overview of the existing methods for GUV production and present our efforts on forming single, free floating vesicles up to several tens of μm in diameter and at high yield in various buffer solutions with physiological ionic strength and pH.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Double emulsion; Electroformation; Giant unilamellar vesicle; Lipid membrane; Microfluidic jetting; Micropipette aspiration; Model membrane system; Swelling